Communication Strategies for Enhancing Visitor Services at the Institut STIAMI Library Central Campus - Pangestu, Danang Aji; Komalawati, Euis (PT FORMOSA CENDEKIA GLOBAL, 2024)
The STIAMI Institute Library plays an important role in providing relevant information to its users. However, challenges such as ineffective communication, limited information technology implementation, and suboptimal service remain. This study aims to understand the communication strategies used by the STIAMI Institute Library to improve visitor services. A qualitative method with a descriptive approach was employed. Data were collected through interviews, observations, and documentation. The results show that internal communication, such as regular meetings and staff collaboration, as well as external communication through social media and online services, increase visitor satisfaction. Additionally, improvements in facilities and technology-based access to information significantly enhance visitor satisfaction. In conclusion, an effective communication strategy is key to improving library services and strengthening its role as an information and education center.